Analysis of Carrying Capacity and Land Capacity for Settlement in Padang Panjang City - Fajrin Ramadya; triyatno triyatno (JURNAL BUANA, 2025)
The city of Padang Panjang, with its undulating topography, faces difficulties in utilizing land for settlement as population growth increases. This study aims to analyze the carrying capacity and accommodating capacity of residential land in the city. Descriptive quantitative research methods with data presented through tables and maps, calculations refer to the Ministry of Environment's 2014 carrying capacity guidelines and the Guidelines for Housing and Settlement Area Development and Development Plan (RP3KP). The results showed that in 2022, Padang Panjang City has a Settlement Carrying Capacity (DDPm) value of > 1. Kelurahan Ganting achieved the highest score of 14.4 and Kelurahan Pasar Baru had the lowest score of 1.8. The area of land suitable for settlement is around 672 hectares, can accommodate 264,309 people with a total of 66,077 housing units. Kelurahan Kampung Manggis stands out with a high capacity, able to accommodate around 34,864 people, while Pasar Baru has the lowest capacity, only 503 people.